Plan estratégico para la cooperativa de ahorro y crédito santa Barbara ltda., de la provincia de Cotopaxi, cantón Pujilí en el periodo 2015 – 2019 - Flores Chicaiza, Nelson David (2016)
The implementation of a strategic plan at Santa Barbara Saving and Loan Credit Union Ltda., will allows knowing the strategic addressing which is understood by the institution philosophy, objects, strategies and the Balanced Scorecard. The efficient dealing tool is important to measure the achievement of each one of the results gotten through the four perspectives, it helps to enforcement the corporative identity and the marketing level. Having the financial service of quality, increasing the financial profits and qualifies human talent to achieve the satisfaction of each one the clients and growing professionally. It is going to improve the administrative department and the efficient use of the resources which provide future changes with the leveraging of each one of the chances into the technological social and economic environment into the credit union.